Predictive value of dual-energy CT assessment of extracellular volume fraction on efficacy of immune checkpoint inhibitors in patients with liver cancer - Lei, Lixing; Huang, Xiaohua; Tang, Lingling; Liu, Nian; Pan, Ke; Liu, Qianqian (Frontiers in Oncology, 2025)
ObjectiveTo investigate the predictive value of dual-energy CT assessment of extracellular volume fraction (ECV) on the efficacy of immune checkpoint inhibitors (ICIs) in patients with liver cancer.MethodsA retrospective analysis was conducted on 179 liver cancer patients who received ICIs in our hospital between November 2023 and February 2025. Patients were divided into a group with excellent treatment efficacy (n=103) and a group with poor treatment efficacy (n=76). Univariate and binary Logistics regression analyses were performed to identify factors influencing treatment efficacy. The predictive value of ECV for the efficacy of ICIs in liver cancer patients was evaluated with receiver operating characteristic (ROC) curve analysis.ResultsThere were statistically significant differences in ECV, CRP, IL-6, NEU, and the status of other anti-tumor treatments between the two groups (P < 0.05). Binary Logistics regression analysis indicated that ECV, CRP, IL-6, and NEU were factors influencing the efficacy of ICIs in liver cancer patients (P < 0.05). ROC analysis showed that ECV had the highest area under the curve (AUC) of 0.839, with a standard error of 0.029 (95% CI: 0.781-0.896), a Youden index of 0.54, sensitivity of 56.58%, specificity of 97.09%, and an optimal cutoff value of 0.45. Patients were grouped based on the optimal critical value of ECV, with the survival probability of patients with ECV ≤ 0.45 being higher than that of patients with ECV > 0.45, showing statistically significant differences (P < 0.05). Patients with ECV ≤ 0.45 also exhibited higher post-treatment immune function indicators compared to those with ECV > 0.45, with statistically significant differences (P < 0.05).ConclusionDual-energy CT assessment of ECV demonstrates good predictive value in the efficacy of ICIs in liver cancer patients, assisting clinical judgment of treatment efficacy.